The association between morphological and ecological characters across a global passerine radiation - Kennedy, Jonathan D.; Marki, Petter Z.; Fjeldså, Jon; Rahbek, Carsten; Derryberry, Elizabeth (The Journal of animal ecology, 2020)
Strong relationships between morphological and ecological characters are commonly predicted to reflect the association between form and function, with this hypothesis being well supported in restricted taxonomic and geographical contexts. Conversely, among broader sets of species, ecological variables have been shown to have limited power to explain morphological variation. To understand these apparent discrepancies, for a large and globally distributed passerine radiation, we test whether (a) the character states of four ecological variables (foraging mode, diet, strata and habitat) have different morphological optima, (b) ecological variables explain substantial variance in morphology and (c) ecological character states can be accurately predicted from morphology. We collected 10 linear morphological measurements for 782 species of corvoid passerines, and assessed (a) the fit of models of continuous trait evolution with different morphological optima for each ecological character state, (b) variation in morphological traits among ecological character states using phylogenetically corrected regressions and (c) the accuracy of morphological traits in predicting species‐level membership of ecological character states using linear discriminant analysis (LDA). Models of morphological evolution with different ecological optima were well supported across numerous morphological axes, corresponding with significant differences in trait distributions among ecological character states. LDA also showed that membership of the ecological categories can be predicted with relatively high accuracy by morphology. In contrast to these findings, ecological variables explain limited amounts of variation in morphological traits. For a global radiation of passerine birds, we confirm that the generation of morphological variation is generally consistent with ecological selection pressures, but that ecological characters are of limited utility in explaining morphological differences among species. Although selection towards different optima means that membership of ecological character states tend to be well predicted by morphology, the overall morphospace of individual ecological character states tend to be broad, implying that morphology can evolve in multiple ways in response to similar selection pressures. Extensive variation in morphological adaptations among similar ecological strategies is likely to be a widespread phenomenon across the tree of life. For a global radiation of passerine birds, the authors demonstrate that the generation of morphological diversity is consistent with ecological selection. Although membership of ecological categories is well predicted by morphology, the morphological variability of character states is broad, implying that divergent morphological forms can evolve from similar selection pressures.